Recurrent pleomorphic adenoma of the parotid gland: A population‐based study with emphasis on re‐recurrence and malignant transformation. Issue 3 (23rd December 2022) - Xu, Wanlin; Zhang, Xu; Wu, Yifan; Zhu, Yun; Liu, Shengwen; Lu, Hao; Yang, Wenjun
Abstract: Background: This study aimed to analyze the prognostic determinants for re‐recurrence and malignant transformation of parotid recurrent pleomorphic adenoma (RPA). Methods: Between January 2011 and December 2020, all the cases of RPA of the parotid gland at our single institution were reviewed. Results: A total of 168 patients were included in this study, with a median age of 41.5 years, and 20 (11.9%) patients developed re‐recurrence during follow‐up. It has been evidenced that recurrence times (single or multiple) was an independent prognostic factor for recurrence‐free survival ( p = 0.0264). A total of 26 (15.48%) patients experienced malignant transformation of parotid RPA, and older age (>45 year old), male sex, and higher clinical tumor staging (T3–T4) were significantly associated with malignant transformation of parotid RPA. Conclusions: Recurrence times was an independent prognostic factor for re‐recurrence of parotid RPA, and older male with high T‐stage may more easily develop malignant transformation.